1999
DOI: 10.1002/(sici)1097-4628(19991220)74:13<3094::aid-app12>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Semibatch emulsion polymerization of butyl acrylate. I. Effect of monomer distribution

Abstract: ABSTRACT:The effects of initial monomer charge on the particle formation and on the rate of polymerization were investigated for semibatch emulsion polymerization of butyl acrylate using sodium lauryl sulfate (SLS) as a surfactant and potassium persulfate (KPS) as an initiator. For the semibatch process with monomer (M) feed, it was found that by varying the monomer distribution ratio between the initial reactor charge and the feed it is possible to alter the contribution of monomer-flooded and monomerstarved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 13 publications
6
45
0
Order By: Relevance
“…In many occasions, the reactor content could be a small fraction of the total reactor volume. The variations in reaction volume are particularly important in semibatch emulsion polymerization reactors where a significant part of the monomer and other ingredients are added to the reactor over the time 23…”
Section: Resultsmentioning
confidence: 99%
“…In many occasions, the reactor content could be a small fraction of the total reactor volume. The variations in reaction volume are particularly important in semibatch emulsion polymerization reactors where a significant part of the monomer and other ingredients are added to the reactor over the time 23…”
Section: Resultsmentioning
confidence: 99%
“…where a s is the area occupied by the surfactant molecule on the surface of the polymer particles, which is 0.43 nm 2 for SDS [18], and N A is Avogadro's constant. D ps is the average diameter of the monomer-swollen particles, which can be calculated by…”
Section: Measurementsmentioning
confidence: 99%
“…Sajjadi [10] showed that in a typical semicontinuous monomer-starved emulsion polymerization, the size of particles and the number of particles can be manipulated by the rate of monomer addition (R a ), surfactant concentration ([S]), and initiator concentration ([I]) or the rate of initiator decomposition (R I ) [17][18][19]. He derived an analytical equation for the formation and growth of nanoparticles in monomer-starved semicontinuous emulsion polymerization of styrene-like monomers, which showed that the number of particles (N p ) and their volume-average diameter (D v ) at the end of nucleation vary according to the following equations [18,20]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monomer accumulates in the system as monomer droplets and the polymer particles are saturated with the monomer, as in Interval II of a batch process. In the monomer-starved type, the rate of addition is lower than the rate of polymerization and the polymerization reaction occurs in Interval III where particles are not swollen to their maximum size, leading to the production of small sized, high solid content latexes [56][57][58][59][60][61][62][63][64][65][66].…”
Section: Semi-continuous (Or Semi-batch) Processmentioning
confidence: 99%